Die invloed van omgewingstoestande op rypwording, kieming, groeikragtigheid en opbrengs van gesertifiseerde sojaboonsaad - Oellermann, Heinz Ernst (Bloemfontein: Central University of Technology, Free State, 2002)
The objective of this study was to determine the effect of the environment on the quality and yield of seed from different seed lots. Localities with different soil types, soil structures and climates were chosen to grow seed lots of the soybean (Glycine max L. Merril) variety Prima. After harvesting by hand, the seed was analysed for oil, protein and mineral content. Physical quality, germination and vigour tests were also done. There were big differences in the growing conditions and precipitation. Rainfall varied from a high of 956mm for the Komatipoort locality to a low of 149mm for the Delmas locality. The percentage defects varied from 0.5% for Delmas to 78% for Komatipoort and the germination percentage from 94% for Klerksdorp to 16% for Komatipoort. Suitable temperatures and rainfall lead to the infection ofthe disease Phomopsis longicol/a atthe Komatipoort locality. This was the reason for poor germination results and high percentage defects in the seed. Vryheid had the highest protein percentage of 38.53% and Delmas the lowest of 33.34% The harvested seed was planted at Greytown first on the Redgates and Chaileyfarm in a randomized block design in orderto determine germination, vigour and yield for seed from different seed lots multiplied in different soil types and climatic conditions, and now planted under similar climatic conditions. The analyses and comparisons in terms of leaf area index at the early flowering (R2) stage, plant height at harvest mature (R8) stage, pod height at R8 stage and eventual yield, did not reveal any significant differences (P=0.05). No significant differences were recorded for seed yield Yield. The average yield of the Chailey locality however was 1021 .9 kg/ha higher than the average yield ofthe Redgates locality. Growth conditions did dominate the effect of different seed lots. Poor germination and stand also had very little effect on seed yield as demonstrated by the Komatipoort treatment. Although plantpopulation was 150000 plants per hectare lower than the average for both trials, final seed yield were not significantly different (P=0.05) Therefore plant population had no influence on the yield. The author conclude thatfor soil types, soil structures and climatic conditions typical of this study, no effect for seed lot on yield could be demonstrated
Thesis
Keywords: Soybean - Seeds; Agriculture - Environmental aspects; germination; vitality; growing environment